RELATIONSHIP OF MOTIVATION AND AWARENESS WITH SELF-EFFICACY OF UNDERGRADUATE NURSING STUDENTS IN CARDIOPULMONARY RESUSCITATION - Yustina Ni Putu Yusniawati; Ida Rahmawati; I Nyoman Arya Mahaputra (Institute for Research and Community Service of Health Polytechnic of Kerta Cendekia, Sidoarjo, 2022)
Background: Cardiac arrest is an unpredictable incident where the heart stops working very quickly, becoming a major health concern globally, especially during the COVID-19 pandemic. Death occurs when the victim is delayed in obtaining cardiopulmonary resuscitation (CPR). All levels of society, especially undergraduate nursing students, must be able to perform CPR by increasing their ability to become qualified CPR bystanders. Objectives: This research aims to analyze factors related to the self-efficacy of undergraduate nursing students (motivation and awareness) in performing CPR on undergraduate nursing students in Indonesia. Methods: This is quantitative research with a cross-sectional approach, using a purposive sampling technique. Sample in this research 290 students. Data collection was carried out from January 2021 to February 2021 through google form online questionnaire containing: demographic data, the dependent variable which is motivation and awareness, and the dependent variable which is nurse efficacy. Statistical test for bivariate using spearmen rho and multivariate using logistic regression. Results: The results showed that most undergraduate nursing students had good efficacy when facing cardiac arrests, with 166 (57.2%). The results of the binary logistic regression showed that the factors associated with nursing undergraduate efficacy were motivation (OR=1.106 95% CI = 0.497-2,458 p-value 0.000) and awareness (OR = 18.575 95% CI = 7,798-44,245 p-value 0.000). Conclusion: Good efficacy of nursing undergraduate students can be attained through collaboration between student motivation and awareness in performing CPR on victims with cardiac arrest.